Courage And Loss Reflected In Paulo Choelo The Zahir:A Psychoanalytic Approach - Purnaningsih, Heni; , Drs. Abdillah Nugroho, M.Hum; , Nur Hidayat, S.Pd (2013)
The object of this study is The Zahir novel is directed by Paulo Choelo. This study is how the courage and loss are reflected in The Zahir using Psychoanalytic Approach. The researcher proposes to analyze id, ego, and superego in the novel with title The Zahir using Psychoanalytic Approach. There are two objectives of the study. Firstly, it is to analyze the structural elements of The Zahir and secondly is to analyze how the courage and loss based on the psychoanalytic approach. The researcher employs the descriptive qualitative as a type of the research. The data source in this research is divided into two types that are primary data and secondary data. Primary data source is The Zahir novel and secondary data source is any information related to the novel. The writer also gathers information of Pulo Coelho background and his works from many books. The method of collecting data is documentation. The technique of analyzing data in this research paper is descriptive. The result of the study comes to two following conclusions. First, based on structural element in The Zahir, it describes that character and characterization, setting, plot, point of view, style and theme. Second, based on theory courage and loss, It describes loss is problem that causes courage be important in the problems. So, The courage changes new life in the future.